Analisis Hubungan Psikologis Konsumen terhadap Minat Beli pada Rumah Makan Selamat di Bukittinggi - Yimmi Syavardie (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2021)
This research was conducted at the Selamat Bukittinggi Restaurant which has rendang food. This type of research is descriptive research that uses a quantitative approach. This study explains and describes the influence between the psychological variables of consumers as independent variables, on the variable of purchase intention as the dependent variable. The sample in this study was 100 respondents. The data analysis methods used in this study are validity test, reliability test, descriptive analysis, Spearman rank correlation analysis, and coefficient of determination test. The results found that all variables (motivation and perception) had a positive and significant effect on consumers' purchase intention. From the results of the Determinant Coefficient test, the R2 value of 0.504 means that the contribution of the motivation and perception variables to purchase intention is 50% while the remaining 50% is influenced by other variables not included in this study. The calculated z value is greater than the z table, indicating that there is a significant influence between motivation and perception on purchase intention.